Anti-Staphylococcus aureus Activity of Volatile Phytochemicals and Their Combinations with Conventional Antibiotics Against Methicillin-Susceptible S. aureus (MSSA) and Methicillin-Resistant S. aureus (MRSA) Strains - Isidora Nikolic; Verica Aleksic Sabo; Damir Gavric; Petar Knezevic (Antibiotics)
Background: MSSA and MRSA strains are challenging human pathogens that can develop resistance to antibiotics, highlighting the need for alternative antimicrobial agents. Plant metabolites, particularly volatile phytochemicals, may offer promising antimicrobial properties. The aim was to evaluate the antimicrobial and antibiofilm efficacy of various commercial volatile phytochemicals from the terpene and terpenoid groups against reference MSSA and MRSA strains, focusing on synergistic effects in both binary combinations and combinations with antibiotics. Methods: The microdilution method was used to determine the minimum inhibitory concentrations (MICs) for antibiotics and phytochemicals. The checkerboard method assessed synergistic interactions between phytochemicals and between phytochemicals and antibiotics, while the time-kill method was used to confirm these results. Biofilm quantification was performed using the microtiter plate method to evaluate the effects of phytochemicals, antibiotics, and their binary combinations on the eradication of 48-h-old biofilms. Results: Carvacrol and thymol demonstrated the strongest anti-staphylococcal activity, while other terpene compounds showed weaker effects. In binary combinations, carvacrol and thymol exhibited synergy against one MSSA strain (FICI = 0.50) and with tetracycline and chloramphenicol (FICI = 0.28–0.50). Synergy was also noted with streptomycin sulfate against one MRSA strain (FICI = 0.31–0.50) and with other antibiotics, including gentamicin (FICI = 0.25–0.50) and oxacillin (FICI = 0.44). Additionally, effective combinations achieved over 50% biofilm removal at both minimum inhibitory and sub-inhibitory concentrations. Conclusions: Results showed that synergy varies based on strain sensitivity to chemical agents, highlighting their potential for personalized therapy. Despite the difficulty in removing preformed biofilms, the findings highlight the importance of combined treatments to enhance antibiotic effectiveness.